The Dinosaur Renaissance 1960s-80s: A Foundational Episode for the Historiography of Paleoart - Monnin Victor (HoST, 2023)
The “Dinosaur Renaissance” is known as a crucial event in the study of dinosaurs. From sluggish and lizard-like, they came to be conceived and represented as more dynamic animals. This paper argues that the “Dinosaur Renaissance” did not only constitute a significant scientific and artistic shift. Indeed, it can also be interpreted as a foundational episode for the historiography of paleoart. During the “Dinosaur Renaissance,” a growing community of artists and paleontologists promoted the integration of artistic processes in paleontology. They began to actively discuss the historical legacy and future of such integration. The itinerant paleoart exhibition Dinosaurs Past and Present, hosted in eight major cities across North America at the end of the 1980s, can be identified as having played a significant role in setting the foundation for the historiography of paleoart. The “Dinosaur Renaissance” did not only result in revised visual representations of dinosaurs, but also spurred some of the first investigations on the historical relationship between visual arts and paleontology. This article concludes by offering some remarks on how the present historiography of paleoart can continue to build on the efforts made during the “Dinosaur Renaissance” while remaining cognizant of their context. To effectively answer the needs of historians, as well as of paleontologists and paleoartists alike, the growing historiography of paleoart has much to gain in clarifying its own history.